Use of Evolutionary Computing for Predicting Sediment Transport of Malaysian Rivers - Abdul Ghani, Nadiatul; Shahin, Mohamed; Nikraz, Hamid (International Association for Hydro-Environment Engineering and Research, 2011)
Existing available models for predicting the total load of sediment transport are mostly developed based on data of flumes, channels and rivers from the western countries. Therefore, such models may not be valid for predicting the sediment transport of Malaysian rivers due to the significant difference in the hydrological and sediment characteristic conditions. In this paper, the validity of the existing sediment transport models is investigated for the Malaysian rivers. In addition, a new model for the Malaysian rivers that is based on the Evolutionary Polynomial Regression (EPR) is developed and presented. EPR is an emerging and promising technique that has been successfully used in many situations in civil engineering. The performance and predictive ability of the developed EPR model are compared with the available sediment transport models and the results are discussed.